A thermostable Cas12b from Brevibacillus leverages one-pot discrimination of SARS-CoV-2 variants of concern - Nguyen, Long T; Macaluso, Nicolas C; Pizzano, Brianna L M; Cash, Melanie N; Spacek, Jan; Karasek, Jan; Miller, Megan R; Lednicky, John A; Dinglasan, Rhoel R; Salemi, Marco; Jain, Piyush K (EBioMedicine, 2022)
BACKGROUND: Current SARS-CoV-2 detection platforms lack the ability to differentiate among variants of concern (VOCs) in an efficient manner. CRISPR/Cas (Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated) based detection systems have the potential to transform the landscape of COVID-19 diagnostics due to their programmability; however, most of these methods are reliant on either a multi-step process involving amplification or elaborate guide RNA designs. METHODS: Three Cas12b proteins from Alicyclobacillus acidoterrestris (AacCas12b), Alicyclobacillus acidiphilus (AapCas12b), and Brevibacillus sp. SYP-B805 (BrCas12b) were expressed and purified, and their thermostability was characterised by differential scanning fluorimetry, cis-, and trans-cleavage activities over a range of temperatures. The BrCas12b was then incorporated into a reverse transcription loop-mediated isothermal amplification (RT-LAMP)-based one-pot reaction system, coined CRISPR-SPADE (CRISPR Single Pot Assay for Detecting Emerging VOCs). FINDINGS: Here we describe a complete one-pot detection reaction using a thermostable Cas12b effector endonuclease from Brevibacillus sp. to overcome these challenges detecting and discriminating SARS-CoV-2 VOCs in clinical samples. CRISPR-SPADE was then applied for discriminating SARS-CoV-2 VOCs, including Alpha (B.1.1.7), Beta (B.1.351), Gamma (P.1), Delta (B.1.617.2), and Omicron (B.1.1.529) and validated in 208 clinical samples. CRISPR-SPADE achieved 92·8% sensitivity, 99·4% specificity, and 96·7% accuracy within 10-30 min for discriminating the SARS-CoV-2 VOCs, in agreement with S gene sequencing, achieving a positive and negative predictive value of 99·1% and 95·1%, respectively. Interestingly, for samples with high viral load (Ct value ≤ 30), 100% accuracy and sensitivity were attained. To facilitate dissemination and global implementation of the assay, a lyophilised version of one-pot CRISPR-SPADE reagents was developed and combined with an in-house portable multiplexing device capable of interpreting two orthogonal fluorescence signals. INTERPRETATION: This technology enables real-time monitoring of RT-LAMP-mediated amplification and CRISPR-based reactions at a fraction of the cost of a qPCR system. The thermostable Brevibacillus sp. Cas12b offers relaxed primer design for accurately detecting SARS-CoV-2 VOCs in a simple and robust one-pot assay. The lyophilised reagents and simple instrumentation further enable rapid deployable point-of-care diagnostics that can be easily expanded beyond COVID-19. FUNDING: This project was funded in part by the United States-India Science & Technology Endowment Fund- COVIDI/247/2020 (P.K.J.), Florida Breast Cancer Foundation- AGR00018466 (P.K.J.), National Institutes of Health- NIAID 1R21AI156321-01 (P.K.J.), Centers for Disease Control and Prevention- U01GH002338 (R.R.D., J.A.L., & P.K.J.), University of Florida, Herbert Wertheim College of Engineering (P.K.J.), University of Florida Vice President Office of Research and CTSI seed funds (M.S.), and University of Florida College of Veterinary Medicine and Emerging Pathogens Institute (R.R.D.).
Keywords: Humans; RNA, Guide, Kinetoplastida; guide RNA, Kinetoplastida; lidé; SARS-CoV-2; COVID-19; Brevibacillus